Special Education Teachers’ Readiness and Self-Efficacy in Utilization of Assistive Technologies for Instruction in Secondary School - Tosho Bakinde Surajudeen; Ebenezer Sanya Ibironke; Gboyega Ayodeji Aladesusi (Indonesian Journal of Community and Special Needs Education, 2023)
This study determined the Special Education Teachers’ Readiness and Self-Efficacy in Utilization of Assistive Technologies for Instruction in Secondary School, Oyo State. The study adopted descriptive research of the survey type. The population for this study was made up of all special education teachers in Oyo State. Purposive sampling techniques were used to select 119 special education teachers in Oyo-state. Descriptive and Inferential statistics were used to answer the research question and test the stated hypotheses with the aid of statistical product and service solution (SPSS) version 20.0 at a 0.05 level of significance. The findings indicated that special education teachers are ready to use assistive technology for instruction and the teachers have high self-efficacy in the use of assistive technology for instruction.  The study concluded that assistive technology can be used to facilitate teaching and stimulation if appropriately deployed.  Therefore, it was recommended that special Education teachers should be encouraged to deploy assistive technology for learning irrespective of their gender